Accent Beliefs Scale (ABS): Scale Development and Validation. (January 2020) - Hansen, Karolina
People's accents in speech strongly influence how they are perceived by others. The current Accent Beliefs Scale was inspired by work on stigmatization, implicit theories of intelligence, and essentialism. The scale has two dimensions: accent diagnosticity and accent stability. The scale was developed, validated, and applied using a mixed methods approach with a QUAN–qual sequential design. Pretest and Study 1 developed the items, the subscales, and showed that diagnosticity and stability beliefs are independent of each other. Study 2 confirmed the scale's two-factor structure on a large sample and proved its divergent and convergent validity. Study 3 addressed predictive validity and showed that the more perceivers viewed accents as diagnostic of other traits and the more they believed accents can be changed, the worse they evaluated a nonnative speaker with a strong accent. The developed scale can help understanding and predicting negative reactions to nonnative speakers.